Speed ​​the transition and its relationship to accurately correction of jumping Amama handball - Shakir, Saja (Journal of Physical Education, 2010)
The special phsicl properties are very important and essential for the activity which improve the acting level in different sports activities if we want to do any skill full movement we need a high special physical property . this will improve the acting level skillfully so it has basic and important toile in any team of the game such as (volley ball ،Basket ball and hoky ball ) and all the game that need skill full in acting and they all need also group to ply in .all the player need to move fast during the period of the player need to move fast during the period of the rece (game ). The ability of running fast is very important to each player and he must move fast when he attacks against the other team . all these things lead to good results wrhich are very in portent at the end the game to win .this research apply an som players of tenns from the team of women and the researcher makes teste on their running andhich end jumping fast and skill fully which enable them to score goals and fulfill a good resuit in this research we know also the relation and connection between the things that disting with the tennis game specially and accurately . the research also appears this kind of the relation and connection of the running fast test of the players moring and the test of scoring accurately in jumping successfully . it is also obvious the relation will be the same as the moving and acting of the players skill fully